Efficient Identification of Pulsatilla (Ranunculaceae) Using DNA Barcodes and Micro-Morphological Characters - Li, Qiu-jie; Wang, Xi; Wang, Jun-ru; Su, Na; Zhang, Ling; Ma, Yue-ping; Chang, Zhao-yang; Zhao, Liang; Potter, Daniel (Frontiers in Plant Science, 2019)
Pulsatilla (Ranunculaceae) comprises about 40 species, many of which have horticultural and/or medicinal importance. However, the recognition and identification of wild Pulsatilla species is difficult due to the presence of complex morphological characters. DNA barcoding is a powerful molecular tool capable of rapidly and accurately distinguishing between species. Here, we assessed the effectiveness of four commonly used DNA barcoding loci—rbcL (R), trnH-psbA (T), matK (M) and ITS (I)—to identify species of Pulsatilla from a comprehensive sampling group. Among the four barcoding single loci, the nuclear ITS marker showed the highest interspecific distances and the highest rate of correct identification. Among the eleven combinations, the chloroplast multi-locus R+T and R+M+T combinations were found to have the best species discrimination rate, followed by R+M. Overall, we propose that the R+M+T combination and the ITS marker on its own are, respectively, the best multi- and single-locus barcodes for discriminating among species of Pulsatilla. The phylogenetic analysis was able to distinguish species of Pulsatilla to the subgenus level, but the analysis also showed relatively low species resolution. This may be caused by incomplete lineage sorting and/or hybridization events in the evolutionary history of the genus, or by the resolution limit of the candidate barcodes. We also investigated the leaf epidermis of eight representative species using scanning electronic microscopy. The resulting micro-morphological characters were valuable for identification of related species. Using additional genome fragments, or even whole chloroplast genomes combined with micro-morphological data may permit even higher resolution of species in Pulsatilla.